SOCIAL MEDIA ACCESS PATTERNS AND RELIGIOUS EDUCATION AND THE POTENTIAL FOR STUDENT RADICALISM (Case Study of IAIN Pontianak Students) - Mukti, Abdul; Rosdiawan, Ridwan; Supyati, S. Ag., Supyati (The Pontianak State Institute of Islamic Studies, 2024)
Students of IAIN Pontianak are representatives of well-educated young Muslim millennials who are famialiar with social media. Through the Internet, they acquire scientific information as well as socio-religious issues on their demand and reflect their identities. As politicized religious issues and terrorisism contents widely circulated online, the students are susceptible to be radicalized. This article elaborates the correlation between the students’ patterns of social media access and their religious modalities, to radical potentiality. The study indicates that correlation persists significantly among variables assessed.